Prioritizing Usability Factors for Website Usability Improvement: A Case Study of Student Academic Information System at Brawijaya University - Niken Hendrakusma Wardani; Apol Pribadi Subriadi (Institut Teknologi Sepuluh Nopember, 2015)
The importance of usability can determine the success or failure of the web application. Conventional approaches of usability evaluation methods only consider the average score from usability assessment which represents the frequency of problems from users when using the website. Another approach to measure the impact of usability factors can be calculated using the method of Partial Least Square. The case study show that combining between this two approaches (average score of usability assessment and impact of usability factors) can be considered for decision makers in prioritizing factors usability.